Nanyang venture formula 1 - further improvement of the mechanical and aerodynamic system of vehicle - Toh, Yi Xuan (Nanyang Technological University, 2023)
This final Year Project revolves around a larger project, Nanyang Venture Formula (NVF). A two-year project started in 2020 by a group of students to design, develop, produce, and test a life-sized electric Formula 1 inspired automobile named Nanyang Venture Formula 1, which will compete in the annual Formula Society of Automotive Engineers (FSAE) competition in July 2023. The main project's (NVF) purpose is to supply the groundwork for future Nanyang Technological University (NTU) teams to compete in and do well in future FSAE tournaments. Because this is NTU's first time competing, the team set a reasonable aim of clearing the technical inspection (40% pass rate). This FYP detailed the method and manufacturing processes for the front wings and nose cone as part of the front aerodynamic package of NVF-1. The vacuum process is chosen for composite manufacturing, and 3D-printed moulds are used for intricate shapes that are difficult to replicate.